2017
DOI: 10.1186/s12885-017-3056-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary neuroendocrine breast carcinomas are associated with poor local control despite favourable biological profile: a retrospective clinical study

Abstract: BackgroundBreast carcinomas with neuroendocrine features (NEBC) are a very rare entity of mammary neoplasms, WHO classification of which has recently been revised. There are very limited data available about the clinical behaviour and treatment options of NEBC.MethodsWe collected retrospectively patients with NEBC from Oulu and Helsinki University Hospitals in 2007–2015. There were 43 NEBC cases during the period.ResultsThe incidence of NEBC from all breast cancers varied from 0.1% in Helsinki to 1.3% in Oulu.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 12 publications
4
40
0
Order By: Relevance
“…Some very small NEBC series have previously been reported with CD56 expression [19,26]. Higher expression of cytoplasmic CD56 is associated with low proliferation activity of NEBC, which is a typical expression pattern when comparing NEBC to IDC [2].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some very small NEBC series have previously been reported with CD56 expression [19,26]. Higher expression of cytoplasmic CD56 is associated with low proliferation activity of NEBC, which is a typical expression pattern when comparing NEBC to IDC [2].…”
Section: Discussionmentioning
confidence: 99%
“…NEBC are a rare entity, typically ER-positive and HER2-negative, and frequently resemble luminal A type breast cancers [24]. Nevertheless, NEBC appear to have high locoregional failure rates despite adequate adjuvant therapies [2]. A recent paper with 18 NEBC cases suggested that NEBC have a distinct genetic landscape compared to luminal-type breast cancers, with an enrichment for FOXA1 and TBX3 mutations [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations